The Ototoxicity of Antimalarial Drugs—A State of the Art Review - Jozefowicz-Korczynska, Magdalena; Pajor, Anna; Lucas Grzelczyk, Weronika (Frontiers in Neurology, 2021)
This state of art review summarized the knowledge about the occurrence of hearing and/or balance disorders after antimalarial drugs treatment. The update on clinical applications of antimalarials, their mechanisms of ototoxicity and monitoring of ototoxicity was presented. Studies with a larger number of patients and those in which auditory function was assessed using audiological tests were analyzed. Antimalarials are used not only in the treatment and prevention of malaria but there were repurposed for other diseases like autoimmune, rheumatic, some viral diseases and cancers. In addition to old antimalarial drugs with known ototoxicity, such as quinoline derivatives, new synthetic antimalarial agents, mainly artemisinin derivatives, are currently used, the ototoxicity of which is not well understood. The audiovestibular adverse effects varied depending on the medication itself, its dose, route of administration as well as drug combination, treated disease and individual predispositions of the patient. As ototoxicity manifestations of antimalarial drugs, dizziness was commonly reported side effect while vestibular symptoms, hearing loss and tinnitus were observed much less frequently, most of these symptoms were reversible. Early identification of ototoxic hearing loss is critical to introducing possible alternative treatment with less ototoxic medications, therefore monitoring systems of those drugs ototoxic side effects are much needed.